2018
DOI: 10.1177/0145482x1811200304
|View full text |Cite
|
Sign up to set email alerts
|

The Perspectives of Teachers and Paraeducators on the Relationship between Classroom Clutter and Learning Experiences for Students with Cerebral Visual Impairment

Abstract: Introduction Cerebral visual impairment (CVI) typically affects children's overall functioning in visually cluttered environments. This study aims to consider whether the removal of classroom clutter ameliorates visual problems and the associated behavioral difficulties for these children. Methods Two classrooms at a special school were de-cluttered. Changes included: covering glass panels with thick black paper; hanging sheets over open shelving; creating areas of blank wall in front of the student to focus a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 8 publications
1
8
0
1
Order By: Relevance
“…These children became more distracted, showed more signs of visual and general fatigue and showed less accurate visually guided movement in their classroom environments. This is in line with the work by McDowell and Budd (2018) and Little and Dutton (2014), who show that by reducing the amount of clutter surrounding a child with more severe CVI, their visual and overall functioning greatly improves. This highlights that the Austin Playing Card Assessment has the potential to detect a number of different visual perceptual difficulties, especially when the assessment is conducted in both quiet and cluttered environments and making appropriate comparisons.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…These children became more distracted, showed more signs of visual and general fatigue and showed less accurate visually guided movement in their classroom environments. This is in line with the work by McDowell and Budd (2018) and Little and Dutton (2014), who show that by reducing the amount of clutter surrounding a child with more severe CVI, their visual and overall functioning greatly improves. This highlights that the Austin Playing Card Assessment has the potential to detect a number of different visual perceptual difficulties, especially when the assessment is conducted in both quiet and cluttered environments and making appropriate comparisons.…”
Section: Discussionsupporting
confidence: 89%
“…Recent research by Josef Zihl (outlined in a study by Zihl and Dutton (2015)), Bennett et al (2018), and Goodale and Milner (2013) has identified key features of visual perceptual difficulties, including random search patterns using darting eye movements (quick, repetitive shifts of gaze to different locations in the visual field), increased search times (especially as the complexity increases), decrease in performance when the number of objects and distractions increase, and slower and more inaccurate reaching and grasping of objects. Research by Little and Dutton (2014) and McDowell and Budd (2018) has also shown that cluttered and noisy environments where there is an overload of visual and auditory information, as well as constant movement of others can negatively impact on visual and overall functioning of children with more severe CVI. These findings suggest that to detect visual perceptual difficulties in less-affected children who have near normal or normal visual acuities, assessments conducted in both quiet and cluttered environments (such as a child’s classroom) to compare the child’s performances, could help identify potential visual issues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…U toku dve nedelje rada u ovakvom okruženju nastavnici su pratili i beležili ponašanje učenika sa CVI. Na osnovu intervjua sa njima istraživači su zaključili da takozvana "crna čvorišta" i eliminacija "vizuelne gužve" pozitivno utiču na vizuelno funkcionisanje, ponašanje i učenje učenika sa CVI (McDowell & Budd, 2018). Iako su ovim istraživanjem obuhvaćeni neki primeri adaptacija sredine već korišćeni u individualnom radu sa decom sa CVI, ono ima značajan doprinos u rešavanju jednog segmenta njihovih inkluzivno-edukativnih potreba.…”
Section: Adaptacija Prostora I Materijalaunclassified
“… 7 Research into strategies to support children with CVI has suggested that providing a less cluttered visual environment may help. 8 9 …”
Section: Introductionmentioning
confidence: 99%